Performance Evaluation Of An Unsignalized Four-Leg Intersection And Traffic Signal Planning Using Ptv Vissim: A Case Study Of Panjalin Intersection, Majalengka - Arief Rijaluddin; Eka Juliar; Kamaludin (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2026)
Panjalin Intersection is a strategic four-leg junction connecting the Cirebon–Bandung national road with the Budur–Paningkiran provincial road in Majalengka Regency. Its unsignalized operation, intensive roadside commercial activity, and increasing peak-hour demand create recurring conflicts and unstable traffic movements. This study evaluates the existing intersection and develops a two-phase traffic-signal alternative using the 2023 Indonesian Road Capacity Guidelines (PKJI 2023) and PTV Vissim microscopic simulation. Primary data consisted of intersection geometry, seven-day classified turning-movement counts, vehicle speeds, and roadside-environment observations. Secondary data included population and road-status information. Under the existing condition, total demand reached 2,604 passenger-car units per hour, while the calculated capacity was 2,747.84 passenger-car units per hour. The resulting degree of saturation was 0.947, exceeding the PKJI design criterion of 0.85; the average intersection delay was 16.946 s/pcu and the upper queue-probability estimate was 71.63%. A two-phase signal plan with a 42-s cycle, 15.38-s green time for Phase 1, and 16.62-s green time for Phase 2 reduced approach degrees of saturation to 0.610–0.681, with an average of 0.649 and an average delay of 14.679 s/pcu. The Vissim scenario comparison also indicated reductions in average queue, maximum queue, stopped vehicles, and average travel time by 46.4%, 44.7%, 51.2%, and 21.7%, respectively. The combined analytical and simulation results show that installing a coordinated two-phase traffic signal is a technically reasonable short-term treatment, provided that signal timing, side friction, and queue development are monitored after implementation.